Mechanisms of Vascular Dysfunction in COPD and Effects of a Novel Soluble Epoxide Hydrolase Inhibitor in Smokers - Yang, Lucy; Cheriyan, Joseph; Gutterman, David D; Mayer, Ruth J; Ament, Zsuzsanna; Griffin, Jules L; Lazaar, Aili L; Newby, David E; Tal-Singer, Ruth; Wilkinson, Ian B (Chest, 2017)
Smoking and COPD are risk factors for cardiovascular disease, and the pathogenesis may involve endothelial dysfunction. We tested the hypothesis that endothelium-derived epoxyeicosatrienoic acid (EET)-mediated endothelial function is impaired in patients with COPD and that a novel soluble epoxide hydrolase inhibitor, GSK2256294, attenuates EET-mediated endothelial dysfunction in human resistance vessels both in vitro and in vivo. Endogenous and stimulated endothelial release of EETs was assessed in 12 patients with COPD, 11 overweight smokers, and two matched control groups, using forearm plethysmography with intraarterial infusions of fluconazole, bradykinin, and the combination. The effects of GSK2256294 on EET-mediated vasodilation in human resistance arteries were assessed in vitro and in vivo in a phase I clinical trial in healthy overweight smokers. Compared with control groups, there was reduced vasodilation with bradykinin (P = .005), a blunted effect of fluconazole on bradykinin-induced vasodilation (P = .03), and a trend toward reduced basal EET/dihydroxyepoxyeicosatrienoic acid ratio in patients with COPD (P = .08). A similar pattern was observed in overweight smokers. In vitro, 10 μM GSK2256294 increased 11,12-EET-mediated vasodilation compared with vehicle (90% ± 4.2% vs 72.6% ± 6.2% maximal dilatation) and shifted the bradykinin half-maximal effective concentration (EC50) (-8.33 ± 0.172 logM vs -8.10 ± 0.118 logM; P = .001 for EC50). In vivo, 18 mg GSK2256294 improved the maximum bradykinin response from 338% ± 46% before a dose to 566% ± 110% after a single dose (P = .02) and to 503% ± 123% after a chronic dose (P = .003). GSK2256294 attenuates smoking-related EET-mediated endothelial dysfunction, suggesting potential therapeutic benefits in patients with COPD. ClinicalTrials.gov; No.: NCT01762774; URL: www.clinicaltrials.gov.